Design Analysis of Kori in Palebahan Ancak Saji at Puri Agung Ubud, Bali - Ni Putu Eka Trisnasari Subrata; Kankan Kasmana (ARTic, 2022)
Balinese Traditional Architecture is an architectural concept used by the Balinese people in designing buildings and is still applied on an ongoing basis today. Traditional Balinese architecture has existed since the days of the Hindu kingdoms in Bali. Puri Agung Ubud is one of the heritages of traditional Balinese architecture during the royal period whose buildings are still well maintained and functioning. The current function of the Puri is not only as a residence for the royal family but also functions as a tourist attraction. The areas that can be visited by tourists are the palebahan ancak saji area and the semanggen area. In palebahan ancak saji there is a kori building, a kori is a building that functions as a door for exit and entry access to other palebahans. Kori has the form of a cecandian building structure with various ornaments on each side. The focus of this research is to analyze the shapes and ornaments used on the kori in the northern part of palebahan ancak saji at Puri Agung Ubud. In this study using a qualitative descriptive method following the study of cultural artifacts. The results of this study are to know the shape and types of ornaments used in the North Kori building. Keywords: Kori; Form; Ornamens; Palebahan Ancak Saji